Effect of Monosodium Glutamate (MSG) and Rice Washing Water as Liquid Fertilizer on Ipomea reptanas L. Poir Plant Height - Rikhma Sari, Dwi Nur; Dian Anitasari, Septarini; Nur Hakiki, Zulfa; Faridatus Solehah, Meilita (Universitas Islam Jember, 2023)
The Ipomea reptans L. Poir plant is a horticultural plant that contains high nutrition and is very popular among the public. Monosodium Glutamate (MSG) is a sodium salt which is very important in the vegetative and generative growth of plants. Rice washing water is one of the domestic wastes that is rarely used and has very good properties for plant growth as an organic liquid fertilizer. This research was prepared based on a Randomized Block Design (RAK) with treatment of MSG concentration combined with rice washing water, namely treatment I (MSG 5 grams + 200 mL rice washing water) and treatment II (MSG 5 grams + 200 mL rice washing water) were carried out repetition 3 times. The parameters observed in this research were the height growth of Ipomea reptans L.Poir plants. Giving MSG combined with rice washing water is the best way to increase the height growth of Ipomea reptanas plants, namely MSG 7.5 grams + 200 mL Rice Washing Water which can be seen with a plant height of 33 cm (6 weeks). Key Words: MSG, Rice Washing Water, Plant Height, Ipomea reptanas L. Poir